A Preparation and Characterization of Chitosan-Silica Membranes and Applications for Creatinine and Urea Transport - Ayuni, Ni Putu Sri; Yuningrat, Ni Wayan; Panjaitan, Yuyunda Sari (Universitas Jenderal Soedirman, 2024)
The main organ that of the urinary system after the main organ functions to filter waste products from the body's metabolism that must be removed through the excretion process is the kidneys. The remaining metabolite compounds that accumulate in the blood are caused by the kidneys being unable to filter and remove uremia toxin compounds such as urea and creatinine from the body. One indication of kidney damage can be seen from levels of creatinine and urea in the blood that exceed normal limits. Urea and creatinine levels can be lowered by improving kidney function, namely by the blood washing process (hemodialysis). In the hemodialysis technique, the price of an artificial kidney or hemodialyzer is very expensive so that kidney failure sufferers require very large costs for treatment. To overcome this problem, alternative natural materials are needed to make membrane artificial kidneys. The aim of the research is (1) to analyze the synthesis and characteristics of membranes and, (2) to apply them for the transport of creatinine and urea using silica chitosan membranes. Characterization includes functional group testing using an Fourier-Transform Infrared (FTIR) spectrophotometer, water absorption test (swelling test), tensile test, and morphology with Scanning Electron Microscope (SEM). The membranes were applied for creatinine transport with varying concentrations of 70, 100, and 130 mg/L. It was also used for transporting urea at various concentrations of 500, 1000, and 1500 mg/L. This study disclosed a window of opportunity to produce novel hemodialysis membranes using bio-based materials. Keywords: Biocompatibility, chitosan, creatinine, hemodialysis, membrane, silica, urea